Organic bipolar disorder: An unusual neuropsychiatric sequelae following right frontotemporal injury - Syed Ummar; Naveen Kumar; Shree Aarthi Ramanathan (Indian Journal of Psychological Medicine, 2016)
Psychiatric disorders are common consequences of traumatic brain injury (TBI). But organic bipolar disorder is a rare entity when compared with other disorders. Here, we report this 49 year old patient with bipolar affective disorder following traumatic brain injury, its presentation and management. Though the pathophysiology of this disorder involves the interaction of factors that precede trauma (eg, genetic vulnerability and previous psychiatric history), factors that pertain to the traumatic injury itself (eg, type, extent, and location of brain damage), in our patient it showed an atypical presentation.